A systematic review of the impact of mindfulness on the well‐being of healthcare professionals. Issue 3 (28th July 2017) - Lomas, Tim; Medina, Juan Carlos; Ivtzan, Itai; Rupprecht, Silke; Eiroa‐Orosa, Francisco José
Abstract : Objective: Among efforts to improve the well‐being of healthcare professionals are initiatives based around mindfulness meditation. To understand the value of such initiatives, we conducted a systematic review of empirical studies pertaining to mindfulness in healthcare professionals. Method: Databases were reviewed from the start of records to January 2016. Eligibility criteria included empirical analyses of mindfulness and well‐being outcomes acquired in relation to practice. 81 papers met the eligibility criteria, comprising a total of 3, 805 participants. Studies were principally examined for outcomes such as burnout, distress, anxiety, depression, and stress. Results: Mindfulness was generally associated with positive outcomes in relation to most measures (although results were more equivocal with respect to some outcomes, most notably burnout). Conclusion: Overall, mindfulness does appear to improve the well‐being of healthcare professionals. However, the quality of the studies was inconsistent, so further research is needed, particularly high‐quality randomized controlled trials.